Novel In Vitro Test Systems and Insights for Transcatheter Mitral Valve Design, Part I: Paravalvular Leakage - Pierce, Eric L. (Ann Biomed Eng, 2018)
While transcatheter mitral valve (TMV) replacement technology has great clinical potential for surgically inoperable patients suffering from mitral regurgitation, no TMV has yet achieved regulatory approval. The diversity of devices currently under development reflects a lack of consensus regarding optimal design approaches. In Part I of this two-part study, a test system was developed for the quantification of paravalvular leakage (PVL) following deployment of a TMV or TMV-like device in pressurized, explanted porcine hearts (N=7). Using this system, PVL rate was investigated as a function of steady trans-mitral pressure (ΔP), TMV shape, and TMV-annular oversizing, using a series of “mock TMV plug” devices. Across all devices, PVL was found to approximately trend with the square of ΔP. PVL rates were approximately 0–15ml/sec under hypotensive pressure, 10–40ml/sec under normotension, and 30–85 ml/sec under severely hypertension. D-shaped devices significantly reduced PVL versus circular devices; however, this effect was diminished when the circular device was oversized to the annulus by 6mm inter-trigonal distance. In conclusion, this steady pressure, in vitro test system was effective to compare PVL performance across TMV-like designs. PVL exhibited complex dynamics in terms of its response to transvalvular pressure and TMV profile.